2022
DOI: 10.1186/s12913-022-08722-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes among patients undergoing total hip replacement in an integrated care system and in a standard care system in Region Stockholm, Sweden

Abstract: Background Coordination, cooperation and efficient use of resources is vital for the health- and social care sector if it is to meet the needs of an aging population. Integrated care is a patient-centred approach to provision of care aiming to improve quality of care and overcome fragmented care through co-productive partnerships and may positively affect quality of care and health outcomes, especially among those in need of highly coordinated care services. Aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“… One publication on nurse‐led heart failure clinics in primary care settings reported that this intervention significantly reduced the number of heart failure‐related hospital admissions, hospital days, and emergency room visits [91]. According to two publications assessing the integrated care model for people aged over 65 years implemented by the TioHundra organization, the care model was associated with a decrease in the rate of emergency department visits [92] and the rate of hospitalization for ambulatory care sensitive conditions [93], compared to pre‐intervention levels. However, the difference was not statistically significant when compared to changes in the rest of Stockholm county [92] and a matched control area [93].…”
Section: Results: Scoping Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“… One publication on nurse‐led heart failure clinics in primary care settings reported that this intervention significantly reduced the number of heart failure‐related hospital admissions, hospital days, and emergency room visits [91]. According to two publications assessing the integrated care model for people aged over 65 years implemented by the TioHundra organization, the care model was associated with a decrease in the rate of emergency department visits [92] and the rate of hospitalization for ambulatory care sensitive conditions [93], compared to pre‐intervention levels. However, the difference was not statistically significant when compared to changes in the rest of Stockholm county [92] and a matched control area [93].…”
Section: Results: Scoping Reviewmentioning
confidence: 99%
“…According to two publications assessing the integrated care model for people aged over 65 years implemented by the TioHundra organization, the care model was associated with a decrease in the rate of emergency department visits [92] and the rate of hospitalization for ambulatory care sensitive conditions [93], compared to pre‐intervention levels. However, the difference was not statistically significant when compared to changes in the rest of Stockholm county [92] and a matched control area [93]. Another article examining TioHundra found that patients undergoing total hip replacement in the integrated care system showed no differences across studied health outcomes compared to those receiving standard care [94].…”
Section: Results: Scoping Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…compared Swedish integrated care and standard care in terms of patient-reported outcomes (EQ VAS score, EQ-5D-3L, hip pain VAS score). Their results showed that 1 year after total hip replacement, the health status of patients in integrated care did not differ significantly from patients in standard care 44 .…”
Section: Discussionmentioning
confidence: 96%